Analysis on the characteristics of precipitation changes in the Yangtze River Basin in recent years. Issue 1 (May 2021) - Yan, Bo; Lu, Zhihua; Yao, Liqiang; Xu, Bin
Abstract: The Yangtze River is China's mother river. In the context of climate change, it is of great practical significance to study the changes in precipitation in the Yangtze River Basin, especially in the event of a catastrophic flood in the Yangtze River Basin in 2020.. Based on the daily data of measured precipitation in the Yangtze River Basin, this study analyzed the trend and sudden change of precipitation, and also analyzed the intra-annual distribution during the year, and obtained the following conclusions: the change trend of the annual precipitation shows increase insignificantly, and the change-point occurred around 2015; the flood season accounts for 82.5% of the annual precipitation; the precipitation in the dry season has a slight increasing trend.